2018
DOI: 10.1186/s12882-018-0978-2
|View full text |Cite
|
Sign up to set email alerts
|

Bilineal inheritance of pathogenic PKD1 and PKD2 variants in a Czech family with autosomal dominant polycystic kidney disease – a case report

Abstract: BackgroundAutosomal dominant polycystic kidney disease (ADPKD) is the most common hereditary renal disorder, leading to end stage renal failure and kidney transplantation in its most serious form. The severity of the disease’s manifestation depends on the genetic determination of ADPKD. The huge variability of different phenotypes (even within a single family) is not only modulated by the two main ADPKD genes (PKD1 and PKD2) but also by modifier genes and the whole genetic background.Case presentationThis is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 39 publications
3
10
0
Order By: Relevance
“…Bilineal inheritance of PKD1 and PKD2 variants is an extremely rare finding and, as expected, disease associated with the presence of two distinct mutations appeared to be more severe than the disease associated with either mutation alone (Pei et al, 2001;Elisakova et al, 2018).…”
Section: Probands With More Than One Variantsupporting
confidence: 72%
“…Bilineal inheritance of PKD1 and PKD2 variants is an extremely rare finding and, as expected, disease associated with the presence of two distinct mutations appeared to be more severe than the disease associated with either mutation alone (Pei et al, 2001;Elisakova et al, 2018).…”
Section: Probands With More Than One Variantsupporting
confidence: 72%
“…Thus far, only the combination of 1 truncating and 1 missense mutation or 2 missense mutations has been described. 4 , 5 , 7 , S6−S11 These reports confirmed that in ADPKD patients, the level of functional polycystin-1 or polycystin-2 affects the age of presentation and the disease progression. In addition, it became clear that bilineal inheritance of a PKD1 and a PKD2 mutation caused more severe disease than either one of them, pin-pointing them as important disease modifiers.…”
Section: Discussionsupporting
confidence: 60%
“…Similarly, more progressive disease was described in a patient with bilineal inheritance of a truncating PKD1 p.(Gln2196∗) and a PKD2 missense mutation p.(Arg420Gly). 5 Compound heterozygotes for 2 PKD1 mutations have been described more frequently, including either one truncating with 1 missense mutation or 2 missense mutations in trans . Overall the phenotypes vary from more or less typical to early onset in utero .…”
Section: Introductionmentioning
confidence: 99%
“…Digenic inheritance can also lead to intrafamilial variability. Thus, co-inheritance of PKD1 and PKD2 variants can yield severe, early-onset ADPKD, whereas family members who harbour only one of the two variants typically present with milder disease 161,162 . Similarly, in families with PKD1and PKD2associated ADPKD, individuals who have mutations in genes associated with other hereditary nephropathies, such as HNF1B 163 and COL4A1 (REF.…”
Section: Phenotypic Heterogeneitymentioning
confidence: 99%